2010
DOI: 10.1111/j.1477-2574.2010.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Rescue policy for discarded liver grafts: a single-centre experience of transplanting livers ‘that nobody wants’

Abstract: Transplantable livers are unnecessarily discarded by the transplant community. External and internal supervision of the activity of each LT programme is urgently needed to guarantee high standards of excellence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 27 publications
1
26
0
6
Order By: Relevance
“…The median hospital stay of this series was 9 days (range: 6-19). The median follow-up was 14 months (range: [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. One patient died on postoperative day 17 due to sepsis without signs or serological evidence of Chagas infection (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median hospital stay of this series was 9 days (range: 6-19). The median follow-up was 14 months (range: [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. One patient died on postoperative day 17 due to sepsis without signs or serological evidence of Chagas infection (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In Argentina, despite the implementation of the MELD score allocation system in 2005, the mortality of patients on the liver waiting list is increasing, and has reached 15% and 25% for elective and emergency candidates, respectively (2,3). This scenario has forced our LT team to relax the deceased donor selection criteria, expanding the liver pool to include those organs from T. cruzi-infected donors (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The paradox is that these organs are most susceptible to the consequences of preservation related injury (10)(11)(12). Many ECD livers are turned down by the recipient transplant team because of the inherent risk of preservation injury with limited available preservation technologies (7,13).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that suboptimal livers present increased vulnerability to ischemia/reperfusion injury (IRI) and are associated with poorer posttransplant outcomes . It has been observed that frequently ECD livers are not used for transplantation as a consequence of the intrinsic poor outcome risk, especially in relation to long ischemia time and mainly because of limited available preservation options . Therefore, preservation methods for suboptimal livers need to be further explored and validated …”
mentioning
confidence: 99%